2018
DOI: 10.1097/ncc.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Support Groups Among Older Breast Cancer Survivors

Abstract: Structural changes can benefit existing models of support groups including how and when support needs and services are discussed with survivors and a shift toward the inclusion of practical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Many non-attendees had negative pre-conceived ideas of the support group model of care, including concerns about spreading misinformation and the potential emotional challenges of a metastatic-speci c group, such as confronting the deterioration and death of other group members. These issues have been discussed previously in other studies on support groups for MBC [19,40], and have also been reported amongst EBC survivors [43]. Interestingly, in our study, the participants who consciously chose not to attend a support group had no previous experience with faceto-face MBC groups.…”
Section: Discussionsupporting
confidence: 66%
“…Many non-attendees had negative pre-conceived ideas of the support group model of care, including concerns about spreading misinformation and the potential emotional challenges of a metastatic-speci c group, such as confronting the deterioration and death of other group members. These issues have been discussed previously in other studies on support groups for MBC [19,40], and have also been reported amongst EBC survivors [43]. Interestingly, in our study, the participants who consciously chose not to attend a support group had no previous experience with faceto-face MBC groups.…”
Section: Discussionsupporting
confidence: 66%
“…Both support groups and group therapy have been demonstrated to be effective in reducing psychological distress in a variety of populations. 13 , 14 Group therapy, in which individuals come together to undergo psychotherapy under the supervision of a professional, has been demonstrated to treat psychological symptoms including depression and anxiety in individuals living with Parkinson’s disease. 14 Support groups, which differ from group therapy in that individuals come together to share their perspectives on a similar experience, have been demonstrated to be effective in reducing psychological distress and other psychological symptoms in a variety of populations.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated found that support groups can be used to foster a sense of control and provide information to cancer survivors, as well as improve self-care activities in COPD patients who attend in-person support groups. 13 , 15 Research has also demonstrated that support groups offered virtually through social media can be effective in providing a platform for individuals living with chronic disease to obtain quick information and social support. 16 …”
Section: Introductionmentioning
confidence: 99%